Zebrafish as model organisms for studying drug‐induced liver injury - Vliegenthart, A. D. Bastiaan; Tucker, Carl S.; Del Pozo, Jorge; Dear, James W. (British journal of clinical pharmacology, 2014)
Drug‐induced liver injury (DILI) is a major challenge in clinical medicine and drug development. New models are needed for predicting which potential therapeutic compounds will cause DILI in humans, and new markers and mediators of DILI still need to be identified. This review highlights the strengths and weaknesses of using zebrafish as a high‐throughput in vivo model for studying DILI. Although the zebrafish liver architecture is different from that of the mammalian liver, the main physiological processes remain similar. Zebrafish metabolize drugs using similar pathways to those in humans; they possess a wide range of cytochrome P450 enzymes that enable metabolic reactions including hydroxylation, conjugation, oxidation, demethylation and de‐ethylation. Following exposure to a range of hepatotoxic drugs, the zebrafish liver develops histological patterns of injury comparable to those of mammalian liver, and biomarkers for liver injury can be quantified in the zebrafish circulation. The zebrafish immune system is similar to that of mammals, but the zebrafish inflammatory response to DILI is not yet defined. In order to quantify DILI in zebrafish, a wide variety of methods can be used, including visual assessment, quantification of serum enzymes and experimental serum biomarkers and scoring of histopathology. With further development, the zebrafish may be a model that complements rodents and may have value for the discovery of new disease pathways and translational biomarkers.